Two new benzoic acid derivatives from endophytic fungus Aspergillus versicolor. Issue 1 (22nd December 2021) - Ye, Yanqing; Chen, Yanjun; Hou, Yuting; Yu, Hongmei; Zhu, Lijun; Sun, Yanqi; Zhou, Min; Chen, Yijian; Dong, Miao
Abstract: Two new benzoic acid derivatives, named methyl(S)-3-hydroxy-4-(2- hydroxy -6-methylheptan-2-yl)benzoate (1 ) and 2-hydroxy-3-(6- hydroxy-6-methylhept-1-en-2-yl)benzoic acid (2 ), were isolated from the ethanol extract of an endophytic fungus Aspergillus versicolor derived from the medicinal plant Euphorbia royleana . The structures of compounds (1 –2 ) were elucidated using NMR and MS methods. Graphical Abstract: